Antibacterial Activity of Alkaloid Fractions from Berberis Microphylla G. Forst and Study of Synergism with Ampicillin and Cephalothin - Urzua-Moll, A (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Berberis microphylla is a native plant that grows in Patagonia and is commonly used by aboriginal ethnic groups in traditional medicine as an antiseptic for different diseases. The present study evaluated the antibacterial and synergistic activity of alkaloid extracts of B. microphylla leaves, stems and roots used either individually or in combination with antibiotics against Gram-positive and Gram-negative bacteria. The in vitro antibacterial activities of leaf, stem and root alkaloid extracts had significant activity only against Gram-positive bacteria. Disc diffusion tests demonstrated that the root extract showed similar activity against B. cereus and S. epidermidis compared to commercial antibiotics, namely ampicillin and cephalothin, and pure berberine, the principal component of the alkaloid extracts, was found to be active only against S. aureus and S. epidermidis with similar activity to that of the root extract. The minimum inhibitory concentrations (MICs) of the alkaloid extracts ranged from 333 to 83 μg/mL, whereas minimum bactericidal concentrations (MBCs) varied from 717 to 167 μg/mL. In addition, synergistic or indifferent effects between the alkaloid extracts and antibiotics against bacterial strains were confirmed. © 2016 by the authors; licensee MDPI, Basel, Switzerland.